Surface Contamination Of Covid-19: How Long Can The Virus Last? - Yusnianingsih, Cuay; Evangelina, Shannon Marcella (Medicinus, 2019)
The novel coronavirus, which is now known as COVID-19, has caused a global pandemic. It is known that the main transmission routes of the novel coronavirus are through droplets, close human-to-human contact, and contact with inanimate surfaces contaminated by the virus. Thus, it is important to find out how long SARS-CoV-2 can remain viable on different surfaces. A study by van Doremalen et al. (2020) found that SARS-CoV-2 can remain viable for up to 72 hours on plastic and stainless steel surfaces, 4 hours on copper, and 24 hours on cardboard. Chin et al. (2020) reported that SARS-CoV-2 could persist on wood and cloth for 2 days, and could last for 4 days on glass and banknotes. These findings indicate that viral contamination of object surfaces is an important and dangerous factor in spread of disease, emphasizing the urgent need for prevention strategies against transmission of infection through contact with inanimate surfaces.